2023
DOI: 10.1038/s41564-023-01326-w
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic mapping of microbial and host traits reveals production of immunomodulatory lipids by Akkermansia muciniphila in the murine gut

Abstract: The molecular bases of how host genetic variation impacts the gut microbiome remain largely unknown. Here we used a genetically diverse mouse population and applied systems genetics strategies to identify interactions between host and microbe phenotypes including microbial functions, using faecal metagenomics, small intestinal transcripts and caecal lipids that influence microbe–host dynamics. Quantitative trait locus (QTL) mapping identified murine genomic regions associated with variations in bacterial taxa;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 87 publications
0
19
0
Order By: Relevance
“…F2 surface/cave hybrids have been used in numerous quantitative trait loci (QTL) mapping studies to identify genetic changes associated with cavefish evolution (Gross et al, 2014;Klaassen et al, 2018;Protas et al, 2007;Riddle et al, 2021;Warren et al, 2021). Using microbiome composition as a trait for QTL mapping in mice has revealed genomic regions associated with the abundance of bacterial taxa in the intestine (Zhang et al, 2023).…”
Section: Feasibility Of Genetically Mapping Microbiome Composition In...mentioning
confidence: 99%
“…F2 surface/cave hybrids have been used in numerous quantitative trait loci (QTL) mapping studies to identify genetic changes associated with cavefish evolution (Gross et al, 2014;Klaassen et al, 2018;Protas et al, 2007;Riddle et al, 2021;Warren et al, 2021). Using microbiome composition as a trait for QTL mapping in mice has revealed genomic regions associated with the abundance of bacterial taxa in the intestine (Zhang et al, 2023).…”
Section: Feasibility Of Genetically Mapping Microbiome Composition In...mentioning
confidence: 99%
“…A very recent study has identified A. muciniphila as a major source of another group of N -acyl amines called ornithine lipids (OLs) in the gut [66]. OLs are well characterized in free-living bacteria and these lipids resemble GlyLs except that glycine has been replaced with the amino acid ornithine [11].…”
Section: N-acyl Amines Produced By Members Of the Bacteroidota Functi...mentioning
confidence: 99%
“…Distinguishing between these explanations will be left for future investigations. QTL mapping has been performed previously in DO mice but never at multiple ages 50,62 .…”
Section: Geneticsmentioning
confidence: 99%